Conceptual Analysis of Marketing Management in Digital Companies: A Systematic Literature Review - I Dewa Gede Aristana; I Putu Hendika Permana (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2026)
This systematic review of 50 global studies analyzes the practical applications of marketing management across diverse digital sectors. The study evaluates marketing strategies, technology integration, and consumer engagement tactics using qualitative and quantitative methodologies. Findings reveal that while advanced technologies like AI, AR/VR, and big data enhance personalization, their impact is often hindered by privacy concerns and integration barriers. Comparative analysis underscores the necessity of sector-specific strategies and culturally localized approaches. Although personalized content and influencer collaborations drive engagement, their effectiveness is limited by consumer skepticism and measurement challenges. Furthermore, organizational resistance and skill gaps remain significant implementation hurdles. This review concludes that an integrated, adaptive framework is essential for strategic decision-making and theoretical development in evolving digital markets.